Bystander participation behaviour, leadership styles and leader-member exchange on innovative capability / Nesin @ Elizabeth Kinat - Kinat, Nesin @ Elizabeth (Institute of Graduate Studies, UiTM, 2018)
Innovative capability is one of the requirements for organizational success and survival in the competitive environment. For many years, researchers and scholars have been trying to understand innovative capability achieved by different organizations, work groups and employees vary and how innovative capabilities are developed in an organization. Understanding why some organizations are more innovative than others raised a few questions such as what factors influence innovative capability, what are the paths and recipes for success towards innovative capability? Therefore, the aims of the study were to examine the relationship between bystander participation behaviour and leadership styles of Pygmalion and Machiavellian on innovative capability. Additionally, the study aims to examine the mediating effect of leader-member exchange on the relationship between bystander participation behaviour and leadership styles on innovative capability. This study proposed in integrating the concepts of bystander participation behaviour and leadership styles of Pygmalion and Machiavellian and leader-member exchange on innovative capability in the Malaysian hotel industry…